2022
DOI: 10.1108/cg-10-2021-0389
|View full text |Cite
|
Sign up to set email alerts
|

Does corporate governance induce green innovation? An emerging market evidence

Abstract: Purpose This study aims to investigate the effect of corporate governance (CG) mechanisms (board size, independent commissioner and ownership concentration) on green innovation (GI) in publicly traded companies of Indonesia as an emerging market. Design/methodology/approach Archival data relating to CG and GI were collected for five years (2016–2020). A total of 640 observations were obtained and analyzed using a random effect model. Findings The results indicate that effective governance mechanisms can en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 64 publications
4
25
0
Order By: Relevance
“…Therefore, companies increase profits in an ethical and environmentally responsible manner to meet the interests of the green economy. A similar finding is also suggested by previous studies (see Amore and Bennedsen, 2016 ; Asni and Agustia, 2022 ). This means that corporate governance is an essential organ in green development by encouraging green investment and innovation.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, companies increase profits in an ethical and environmentally responsible manner to meet the interests of the green economy. A similar finding is also suggested by previous studies (see Amore and Bennedsen, 2016 ; Asni and Agustia, 2022 ). This means that corporate governance is an essential organ in green development by encouraging green investment and innovation.…”
Section: Resultssupporting
confidence: 92%
“…The results show the corporate governance index between positive moderates in Malaysian green innovation practices but is insignificant in Indonesia's green innovation practices. There is a limited study that has explored this relationship in the Malaysian context, but the direct relationship between board characteristics such as board size, independent commissioners, and ownership and green innovation in an emerging market is reported as positive (Asni and Agustia 2022). However, our study explored the highest corporate governance characteristic, which resulted in positive in Malaysia but insignificant in the Indonesian context.…”
Section: Moderationmentioning
confidence: 71%
“…Consequently, Fu [110], [111] recommended a positive role of independent directors in innovative performance. Nevertheless, some researchers found that concentrated ownership could facilitate sustainable innovation, since large stockholders have the power and incentive to encourage management toward innovation [112,113]. In view of the foregoing, this research posits the following hypotheses: H5: Corporate governance enhances sustainability performance in the Bangladeshi manufacturing industry.…”
Section: Corporate Governance Performance Innovation Performance and ...mentioning
confidence: 93%